2008
DOI: 10.1007/s10531-008-9517-y
|View full text |Cite
|
Sign up to set email alerts
|

Arthropods in biodiversity hotspots: the case of the Phytoseiidae (Acari: Mesostigmata)

Abstract: The biodiversity hotspot concept was defined by Myers in 1988 to determine priority areas for conservation. They have high endemism levels and have lost more than 70% of their original vegetated area. To date, there is little information on arthropod diversity in these zones. This work focuses on the biodiversity of the Phytoseiidae (Acari), one of the best known among the order Mesostigmata, in these threatened areas. These mites are usually predators and they are worldwide spread. Geographic distribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…In conclusion, the results suggest that few Phytoseiidae species are endemic from Cerrado, a fact also pointed out by Tixier and Kreiter (2009). However, due to the small number of surveys and the high rate of endemic plants in this biome (Myers et al 2000), these results show probably only a fraction of the real diversity of phytoseiid in the region, since the richness of animal groups tend to increase as plant diversity increases (Brose 2003;Dennis et al 1998;MacArthur and MacArthur 1961).…”
Section: Discussionmentioning
confidence: 59%
“…In conclusion, the results suggest that few Phytoseiidae species are endemic from Cerrado, a fact also pointed out by Tixier and Kreiter (2009). However, due to the small number of surveys and the high rate of endemic plants in this biome (Myers et al 2000), these results show probably only a fraction of the real diversity of phytoseiid in the region, since the richness of animal groups tend to increase as plant diversity increases (Brose 2003;Dennis et al 1998;MacArthur and MacArthur 1961).…”
Section: Discussionmentioning
confidence: 59%
“…Is it because species of this sub-genus have not been found yet in this province? In our opinion this hypothesis is weakly sustained, as the number of surveys carried out in the Neotropics is much higher than in other areas (Moraes et al 2004;Tixier et al 2008a;Tixier and Kreiter 2009). We could thus suggest other hypotheses as (i) species of this sub-genus did not colonize this province or (ii) have been extinct.…”
Section: Discussionmentioning
confidence: 72%
“…Entling et al (2010) discussed other mechanisms to explain the spider body size pattern observed: starvation resistance, predation pressure, intraguild interference, phylogenetic relationships. The proportion of rare species is expected to be higher in the tropics (Price et al 1995); we can wonder if this is due to the smaller size of phytoseiids at those latitudes or to the fact that higher habitat diversity in the tropics favours speciation and the existence of rare species in rare habitats (endemism) (Gaston 2000;Meier and Dikow 2004;Mao and Colwell 2005;Tixier and Kreiter 2009). Tropical forests are characterized by diverse assemblages of plant and animal species compared to temperate forests.…”
Section: Number Of Descriptions Over Time and Species Sizementioning
confidence: 99%
“…Tropical forests are characterized by diverse assemblages of plant and animal species compared to temperate forests. In regards to the close relationships largely reported between phytoseiids and plant support (Karban et al 1995;Walter 1996;McMurtry and Croft 1997;Kreiter et al 2002;Tixier and Kreiter 2009), plant diversification in such areas could affect phytoseiid diversity and speciation, limiting gene flow. …”
Section: Number Of Descriptions Over Time and Species Sizementioning
confidence: 99%
See 1 more Smart Citation